Titanium dioxide aggregating nanoparticles induce autophagy and under-expression of microRNA 21 and 30a in A549 cell line: A comparative study with cobalt(II, III) oxide nanoparticles. (August 2017) - Alinovi, Rossella; Goldoni, Matteo; Pinelli, Silvana; Ravanetti, Francesca; Galetti, Maricla; Pelosi, Giorgio; De Palma, Giuseppe; Apostoli, Pietro; Cacchioli, Antonio; Mutti, Antonio; Mozzoni, Paola
Abstract: The toxicity of TiO2 nanoparticles (NPs) is controversial, while it is widely accepted for Co3 O4 NPs. We present a comparative study concerning the uptake of these NPs and their effect on cytoplasmic organelles and autophagy in a human lung carcinoma cell line (A549), including assays on the expression of autophagy-related microRNAs. The NP accumulation caused a fast dose- and time-dependent change of flow cytometry physical parameters particularly after TiO2 NP exposure. The intracellular levels of metals confirmed it, but the Co concentration was ten times higher than that of Ti. Both NPs caused neither necrosis nor apoptosis, but cytotoxicity was mainly evident for Co3 O4 NPs in the first 72 h. TiO2 NPs caused autophagy, contrarily to Co3 O4 NPs. Furthermore, a significant and persistent downregulation of miRNA-21 and miRNA-30a was observed only in TiO2 NPs-treated cultures. The expression of miRNA-155 was similar for both NPs. Oxidative stress was evident only for Co3 O4 NPs, while both NPs perturbed endoplasmic reticulum and p-53 expression. In conclusion, the oxidative stress caused by Co3 O4 NPs can influence energy homeostasis and hamper the ability to detoxify and to repair the resulting damage, thus preventing the induction of autophagy, while TiO2 NPs elicit autophagy also under sub-toxic conditions. Highlights: Intracellular Co was higher than Ti, Co3 O4 NPs were more dispersed. Co3 O4 NPs were cytotoxic after 24 h–exposure, whereas TiO2 NPs only later. Only TiO2 NPs induced authopagy. Only TiO2 NPs induced a persistent down-regulation of miRNA-21 and miRNA-30a. Co3 O4 NPs induced Oxidative stress. Both NPs perturbed ER and p-53 expression.